2014
DOI: 10.1002/pro.2532
|View full text |Cite
|
Sign up to set email alerts
|

Trypsinogen activation as observed in accelerated molecular dynamics simulations

Abstract: Serine proteases are involved in many fundamental physiological processes, and control of their activity mainly results from the fact that they are synthetized in an inactive form that becomes active upon cleavage. Three decades ago Martin Karplus's group performed the first molecular dynamics simulations of trypsin, the most studied member of the serine protease family, to address the transition from the zymogen to its active form. Based on the computational power available at the time, only high frequency fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Starting from a model of trypsin with the Nterminus artificially removed from the "Ile cleft", we were able to observe this insertion event in long aMD simulations. 6 As with thrombin, all crystallographically determined structures of trypsin have the N-terminus of the heavy chain buried (Protein Data Bank). It will be interesting to see whether solution analyses, perhaps by NMR, can reveal the dynamics of this critical region.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a model of trypsin with the Nterminus artificially removed from the "Ile cleft", we were able to observe this insertion event in long aMD simulations. 6 As with thrombin, all crystallographically determined structures of trypsin have the N-terminus of the heavy chain buried (Protein Data Bank). It will be interesting to see whether solution analyses, perhaps by NMR, can reveal the dynamics of this critical region.…”
Section: ■ Discussionmentioning
confidence: 99%
“…This salt bridge is thought to promote the formation of a correctly assembled S1 pocket of the active site and thereby full proteolytic activity. Using accelerated molecular dynamics (aMD) simulations, we recently showed that the N-terminus of trypsin inserts from a trypsinogen-like state into this pocket and remains in the pocket once inserted, indicating that the N-terminus is more stable inside the pocket than out . All crystal structures of α-thrombin show the N-terminus in this inserted conformation (Protein Data Bank).…”
mentioning
confidence: 99%
“…More recently, the spontaneous insertion of Ile16 has been observed in an accelerated molecular dynamics, similarly to what was seen for PC1 and PC2 during our analysis. The Asp194 loop transition as seen for seen in PC 1 during the hybrid elastic network Brownian dynamics simulation was not observed in the accelerated molecular dynamics simulations . Given the very coarse level of detail of our simulations, further studies are needed in order to better understand these mechanisms.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, three loop segments, activation loop 1, 2, and 3 (AL1–3), undergo stabilization [ 19 , 22 ]. The N-terminal insertion of trypsinogen activation has even been observed previously using accelerated molecular dynamics simulations [ 23 ]. While the activation transition of FVII is known to follow the same hallmark steps as trypsinogen-trypsin for it become catalytically active, many important details concerning FVII and the zymogen-like FVIIa are lacking.…”
Section: Introductionmentioning
confidence: 80%
“…It is unclear whether this regulatory framework is evolutionarily conserved among all species carrying FVIIa, something that has recently sparked some debate [ 69 , 70 , 71 ]. From the literature, we know that the energetic origins of the conformational changes induced by N-terminus insertion are both electrostatic and hydrophobic [ 23 , 72 , 73 ]. Thus, the zymogen-to-enzyme activation transition can be considered a cooperative process with distinct energetic and entropic contributions, making it difficult to delineate adequately on the basis of static structures.…”
Section: Resultsmentioning
confidence: 99%